The essence of the training of future elementary school teachers on the safety of life activities - Ismailjon Rakhmanov Alisher Ogli (Open Academia, 2023)
Based on the requirements of the current stage of development, the inclusion of such a subject as "Fundamentals of life safety" in the basic curricula of general education schools promoted the task of training teachers in the field of life safety, a qualified teacher "Life safety " should have theoretical, practical and methodological training on the course, which allows to train schoolchildren in the main subject, taking into account the possibility of problems in the field of life safety.
Keywords: Basics of life safety; Life safety.